Toxic Spaces, Community Voices, and the Promise of Environmental Human Rights: Lessons on the Owino Uhuru Pollution Incident in Kenya. Issue 4 (1st October 2020) - Mwanza, Rosemary
ABSTRACT: Since 2016, the residents of Owino Uhuru, an informal settlement in Kenya, have been embroiled in an effort to obtain justice for harm suffered as a result of pollution by a lead-acid smelting plant. The lead-acid smelting plant was operated by the now defunct Metal Refineries Limited from 2007 until its closure in 2014. In 2016, a class action was filed on behalf of the members of the community. In an August 2020 judgement that has since been appealed by the state, the High Court found in favour of the residents of Owino Uhuru, declaring that the pollution incident constituted violations of the right to life, health, water, and a clean and healthy environment. This article shows that despite that outcome, the environmental human rights dimension of the pollution incident is more expansive that the petition and the ensuing judgement suggest. These violations occurred against a backdrop of a near-exhaustive bill of rights. The apparent gap between the promise embodied by environmental human rights and the lived experience of those negatively impacted by the pollution incident provides a focal point to reflect on the potential and limits of environmental human rights in Kenya's legal context.